Análisis de la viabilidad de un sistema solar fotovoltaico conectado a red y autónomo para la emisora, corporación radial voz del lago (2022)
Solar energy can be harnessed through photovoltaic installations that provide a more environmentally friendly and potentially cost-effective power alternative in the long run. This degree study analyzes the feasibility of an On-Grid and Off-Grid photovoltaic system for the Voz del Lago Radio Corporation, a community radio station that provides radio services to the community of the municipality of Aquitaine in the department of Boyacá